The role of miR-10a-5p in LPS-induced inhibition of progesterone synthesis in goose granulosa cells by down-regulating CYP11A1 - Guo, Xinyi; An, Hao; Guo, Rihong; Dai, Zichun; Ying, Shijia; Wu, Wenda (Frontiers in Veterinary Science, 2024)
The poultry ovary is a preferred target for E. coli and Salmonella infection of tissues, and lipopolysaccharide (LPS) is a critical molecule in infecting the organism and interfering with cell function, invading the ovaries through the cloaca and interfering with progesterone (P4) secretion by follicular granulosa cells (GCs), seriously affecting the health of breeding geese. miRNAs are small, non-coding RNAs with a variety of important regulatory roles. To investigate the mechanism of miR-10a-5p mediated LPS inhibition of progesterone synthesis in goose granulosa cells, Yangzhou geese at peak laying period were selected as experimental animals to verify the expression levels of genes and transcription factors related to progesterone synthesis. In this study, bioinformatic predictions identified miR-10a-5p target gene CYP11A1, and genes and transcription factors related to the sex steroid hormone secretion pathway were screened. We detected that LPS inhibited CYP11A1 expression while increasing miR-10a-5p expression in vivo. Progesterone decreased significantly in goose granulosa cells treatment with 1 μg/mL LPS for 24 h, while progesterone-related genes and regulatory factors were also suppressed. We also determined that the downregulation of miR-10a-5p led to CYP11A1 expression. Overexpression of miR-10a-5p suppressed LPS-induced CYP11A1 expression, resulting in decreased progesterone secretion. Our findings indicated that miR-10a-5p was up-regulated by LPS and inhibited progesterone synthesis by down-regulating CYP11A1. This study provides insight into the molecular mechanisms regulating geese reproduction and ovulation.